The 1954 Excavation of Tombs at Tauchira and Euesperides, Libya - Mitchell, Jodie L.; Blau, Soren (Buried History: The Journal of the Australian Institute of Archaeology, 2019)
In 1954, Walter Beasley, the founder of the Australian Institute of Archaeology (the Institute), financially supported a young Australian archaeologist, G.R.H. Wright, to excavate tombs at Tauchira, near modern Tocra, and Euesperides, in present day Benghazi, Libya. Excavations produced artefacts some of which were sent to the Institute for its museum collection. This paper alerts scholars to the Institute’s holdings from the excavations at Tauchira and Euesperides.